2015
DOI: 10.1371/journal.pone.0124490
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Clearance of TiO2 Nanoparticles in Rats after Intravenous Injection

Abstract: Titanium dioxide (TiO2) nanoparticles are used in many applications. Due to their small size, easy body penetration and toxicological adverse effects have been suspected. Numerous studies have tried to characterize TiO2 translocation after oral, dermal or respiratory exposure. In this study, we focused on TiO2 nanoparticle biodistribution, clearance and toxicological effects after intravenous injection, considering TiO2 translocation in the blood occurs. Using ICP-OES, transmission electron microscopy, and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 29 publications
5
59
0
1
Order By: Relevance
“…59 In any case, most, if not all, investigators incorporate partition coefficients into their nano PBPK models. 10,[17][18][19][20][21][22][24][25][26][27] Here, we found that at least in the case of PAA-PEG, PAA, and gold NPs, the biokinetics cannot be accurately described without introducing a P factor and a similar conclusion was reached by Lin et al 25 The exchange of NPs between blood and organs is strongly influenced by the ability to cross the endothelium. This endothelial permeability varies between organs as a result of differences in the degree of fenestration, as well as phagocytic capacity.…”
supporting
confidence: 72%
“…59 In any case, most, if not all, investigators incorporate partition coefficients into their nano PBPK models. 10,[17][18][19][20][21][22][24][25][26][27] Here, we found that at least in the case of PAA-PEG, PAA, and gold NPs, the biokinetics cannot be accurately described without introducing a P factor and a similar conclusion was reached by Lin et al 25 The exchange of NPs between blood and organs is strongly influenced by the ability to cross the endothelium. This endothelial permeability varies between organs as a result of differences in the degree of fenestration, as well as phagocytic capacity.…”
supporting
confidence: 72%
“…Elimination from the organs varied considerably between the three papers, with different patterns per organ. For the liver, Disdier et al (2015) found a much longer elimination time than Geraets et al (2014) for their particles of 21 nm consisting of 75% anatase and 25% rutile (liver half-life of 265 d vs. 95 d), while Elgrabli et al (2015) found a much shorter elimination time than Geraets et al (2014) for their anatase particles of 525 nm (half-life of 12.6 d in the liver). Overall, the TiO 2 NP estimations used in this assessment fall within the range reported in the current literature.…”
Section: Uncertainties and Assumptionsmentioning
confidence: 90%
“…The recent datasets of Disdier et al (2015) en Elgrabli et al (2015) show roughly comparable TiO 2 NP levels in liver and spleen after one or two days with consideration of the dose applied and observed variation among animals (see Table S2 in the Supplementary Information). Lung levels after one or two days varied among the three papers, while kidney levels of Geraets et al (2014) and Elgrabli et al (2015) were comparable at this timepoint. Elimination from the organs varied considerably between the three papers, with different patterns per organ.…”
Section: Uncertainties and Assumptionsmentioning
confidence: 91%
“…The terminal half-life and total clearance had the following values: 2.91 h and 0.04 L/h, respectively. Titanium in ionic form is quicker eliminated from blood than nano-TiO 2 , whose half-life was determined to be 12.56 days (Elgrabli et al, 2015).…”
Section: Titanium Disposition After Intravenous Administrationmentioning
confidence: 99%
“…Publications that have appeared in recent times usually assess the exposure and health effects that titanium dioxide nanoparticles have on various organs (Cho et al, 2013;Elgrabli et al, 2015;Eydner et al, 2012;Fabian et al, 2008;Geraets et al, 2014;Wang et al, 2007;Wu et al, 2009). There is no information about the behavior of Ti in ionic form in the body.…”
Section: Introductionmentioning
confidence: 99%